Mental health of working adults: their work and their digital literacy - Lim, Jia Hang; Prihadi, Kususanto Ditto; Tan, Crendy Yen Teng (International Journal of Public Health Science (IJPHS), 2025)
The interplay between digital interactions and mental health among working adults is intensifying, driven by the pervasiveness of social media and its potential effects on psychological wellness. This research utilizes a socio-cognitive approach to explore how perceived social support (PSS), work mattering, and work self-efficacy (WSE) mediated by new media literacy (NML) influence general mental health (GMH) in a digital era. Through extensive empirical testing, the study reveals that high levels of NML can directly enhance the positive effects of PSS on GMH, bypassing the need for intermediary states like mattering and self-efficacy. This highlights the critical role of digital skills in moderating social support mechanisms and mental health, suggesting that integrating digital literacy into mental health strategies could be vital for improving workplace well-being in contemporary digitally-focused environments.